Performance of Various Broiler Chicken Hybrids Fed with Commercially Produced Feed Mixtures - Hascik , Peter; Kacaniova, Miroslava; Mihok, Michal; Pochop, Jaroslav; Benczova, Emilia (International Journal of Poultry Science, 2010)
In the experiment, we monitored the impact of a commercially produced feed mixtures on feed utilization and performance of chicken=s hybrids Cobb 500, Hubbard JV and Ross 308, kept under the same conditions. Length of feeding period was 35 days. Values of body weight at the end of the feeding period, daily and weekly increase of weight, daily feed consumption, metabolizable energy, nitrogenous proteins and their consumption in different stages of feeding, feed conversion, metabolizable energy and nitrogenous proteins during the feeding period were statistically evaluated and compared between chickens hybrids. Significant differences (p